2019
DOI: 10.17265/2159-5542/2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The Key Triggers for the Transitioning of Informal SMMEs to Formal SMMEs: A Baseline Survey of the Gauteng Province—South Africa

Abstract: This paper presents the views of 623 informal and formal small, medium, and micro enterprises (SMMEs) operating in the Gauteng Province of South Africa. The objective of the study was to identify challenges and benefits that are experienced by SMMEs during and after the registration process leading to the transition from informal to formal business, the level of awareness by the SMMEs of the registration information, and the procedures in addition to the potential factors that inspire or discourage informal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…In the construction sector, medium, small and micro enterprises consist of a total number between 5 to 200 fulltime equivalents of a paid employee, a total turnover between R200 thousand to R26 million and a total gross asset to the value of R100 thousand ($5,835) to R5 million ($291,703) (fixed property excluded). Many of these small and medium enterprises (Kibuuka and Tustin 2019) face a threat of failure within the first few months, and the lack of strategic planning may prevent them from achieving their full potential (Lestari et al 2020). When starting a business, success or failure is always possible (Anamalay 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the construction sector, medium, small and micro enterprises consist of a total number between 5 to 200 fulltime equivalents of a paid employee, a total turnover between R200 thousand to R26 million and a total gross asset to the value of R100 thousand ($5,835) to R5 million ($291,703) (fixed property excluded). Many of these small and medium enterprises (Kibuuka and Tustin 2019) face a threat of failure within the first few months, and the lack of strategic planning may prevent them from achieving their full potential (Lestari et al 2020). When starting a business, success or failure is always possible (Anamalay 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SMEs have the capacity to reduce unemployment and poverty in the country through job creation and innovations (Kibuuka and Tustin 2019;Nuseeb et al 2021). Small businesses tend to seize opportunities in the market and provide the necessary products and services to satisfy demand (Williams Jr et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMEs cannot afford the services of external accountants due to a lack of business funding and sustainability, which results in poor financial records (Kibuuka & Tustin, 2019). Previous studies have shown that SMEs, particularly in South Africa, struggle to meet their primary financial goals (Bruwer, Beck, Smith, Naidoo, & Green, 2019;Fatoki, 2014;Ngary, Smit, Juan-Pierré & Ukpere, 2014).…”
Section: Effective Management Of Bookkeepingmentioning
confidence: 99%
“…For example, a study on the financial problems that SMMEs encounter highlights how enterprises of varying sizes and forms all struggled to gain either public or private sector funding [17]. Other challenges, faced by Gauteng-based SMMEs, "included poor municipal service delivery, high compliance costs, registration and licensing complexities and high operational costs" [18].…”
Section: Smme Challenges In Gauteng Provincementioning
confidence: 99%